Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1038/s41598-019-49009-z
|View full text |Cite
|
Sign up to set email alerts
|

l-Type Amino Acid Transporter 1 (LAT1/Lat1)-Utilizing Prodrugs Can Improve the Delivery of Drugs into Neurons, Astrocytes and Microglia

Abstract: l -Type Amino Acid Transporter 1 (LAT1/Lat1) is responsible for carrying large, neutral l -amino acids as well as several drugs and prodrugs across the blood-brain barrier (BBB). However, the BBB is not the only barrier that hinders drugs acting effectively within the brain; the brain parenchymal cell membranes represent a secondary barrier for the drugs with intracellular target sites. In this study, expression and function of Lat1 was quantified in mouse primary neuron, astr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 57 publications
3
55
0
Order By: Relevance
“…The efficacy of the drugs and their brain concentrations could be compared at multiple time points. Therefore, LAT1-utilisation can achieve not only targeted brain delivery but also improved intracellular brain delivery, as we have proven in our earlier studies [13,14,36]. Herein, it demonstrated the efficacy of the pro-drug, as measured by reduction in the concentrations of PGE2, which will permit an investigation of the chronic administration of NSAIDs in the treatment of neurodegenerative diseases while avoiding their peripheral adverse effects.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…The efficacy of the drugs and their brain concentrations could be compared at multiple time points. Therefore, LAT1-utilisation can achieve not only targeted brain delivery but also improved intracellular brain delivery, as we have proven in our earlier studies [13,14,36]. Herein, it demonstrated the efficacy of the pro-drug, as measured by reduction in the concentrations of PGE2, which will permit an investigation of the chronic administration of NSAIDs in the treatment of neurodegenerative diseases while avoiding their peripheral adverse effects.…”
Section: Discussionmentioning
confidence: 60%
“…However, the amount of released KPF was quantified in this study from the whole brain tissue and, therefore, we cannot compare how much of KPF was delivered to the target cells, i.e., to activated astrocytes or microglia, in which the target enzymes, COXs, are located. We have previously shown that, although the total brain uptake of PD1 was comparable to KPF itself (K p, brain/plasma 0.0097 and 0.0098, respectively) [36], the LAT1-mediated uptake of PD1 into astrocytes and microglia has been 10-13 and 2-7 times greater, respectively, as compared to KPF [13]. This points to the superiority of LAT1 utilization in transporting the drugs into their intracellular targets and, hence, enhancing their potency and efficacy.…”
Section: In Vivo Prostaglandin E2 Productionmentioning
confidence: 88%
See 3 more Smart Citations